Robust Multi-Object Tracking: A Labeled Random Finite Set Approach - Gardiyawasam Punchihewa, Yuthika Samanmali (Curtin University, 2018)
The labeled random finite set based generalized multi-Bernoulli filter is a tractable analytic solution for the multi-object tracking problem. The robustness of this filter is dependent on certain knowledge regarding the multi-object system being available to the filter. This dissertation presents techniques for robust tracking, constructed upon the labeled random finite set framework, where complete information regarding the system is unavailable.